Cardioprotective Effects of Tannic Acid on Isoproterenol‐Induced Myocardial Injury in Rats: Further Insight into 'French Paradox'. (20th May 2015) - Hu, Xitian; Wang, Hua; Lv, Xinhu; Chu, Li; Liu, Zhenyi; Wei, Xiaogang; Chen, Qincong; Zhu, Lei; Cui, Wei
<x xml:space="preserve">Abstract</x> Tannic acid (TA) is a polyphenolic compound, which has shown diverse pharmacological effects with antimutagenic, anticarcinogenic and antibactericidal properties. However, cardioprotective effects of TA have not been reported. To investigate the protective effects of TA, rats were administered TA for 7 days and then intoxicated with isoproterenol (ISO). Myocardial ischemia injury was indicated by changes in electrocardiographic (ECG) patterns, morphology and cardiac marker enzymes. Furthermore, protein expression levels of c‐fos, c‐jun, tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), cleaved‐caspase‐3 and ‐9 were analyzed by immunohistochemistry, and activities of apoptosis‐related proteins Bax, Bcl‐2, caspase‐3 and nuclear factor kappa B (NF‐κB) were detected by Western blot. Pretreatment with TA ameliorated changes in morphology and ECG, reduced activities of marker enzymes, suppressed overexpression of apoptosis‐related proteins, upregulated expression of antioxidants. Moreover, TA pretreatment contributed to the decrease in ratio of Bax/Bcl‐2, as well as reduced expression of TNF‐α, IL‐1β, caspase‐3, cleaved‐caspase‐3 and ‐9. TA displayed cardioprotective effects, which may be attributed to lowering of Bax/Bcl‐2 ratio, c‐fos and c‐jun expression and inhibition of NF‐κB activation, as well as oxidative stress, inflammation and apoptosis. These findings provide further insight into the 'French paradox' and the mechanisms underlying the beneficial effects of TA. Copyright © 2015 John Wiley & Sons, Ltd.